Realization of neutral white light emission in CaMoO4:4Dy3+ phosphor via Sm3+co-doping - Dixit, P; Chauhan, v; Rai, S B; Pandey, P C (Elsevier Ltd, 2021)
In this paper, Dy3+/Sm3+ co-doped CaMoO4 compounds were synthesized successfully via the auto-combustion method. The tetragonal crystal structure of the phosphors is confirmed by structural study. The vibrational modes are examined by infrared spectroscopy. It has been observed that 4% Dy3+ doped CaMoO4 phosphor shows maximum luminescence intensity. Further, Sm3+ ions are co-doped in 4% Dy3+ doped CaMoO4 for improving their luminescence properties. The Photoluminescence study illustrates energy transfer between [MoO4]−2 groups and Dy3+/Sm3+ ions, under 296 nm excitation. The Dy3+ doped CaMoO4 phosphors emit two sharp peaks at 484 nm (4F9/2→6H15/2) and 574 nm (4F9/2→6H13/2). Further, with Sm3+ co-doping in 4% Dy3+ doped CaMoO4 phosphor, another distinctive emission peak is observed at 647 nm, which is attributed to 4G5/2→6H9/2 electric dipole transition of Sm3+ ion. The Dy3+/Sm3+ co-doped CaMoO4 phosphor gives overall white light emission. For 3% Sm3+ co-doped CaMoO4:4Dy3+ phosphor, white light is obtained with the CCT value of 4439 K. Hence, the prepared phosphor might be used in white lighting diode applications.
Prashant Dixit and Vaibhav Chauhan are thankful to UGC, India, and CSIR, India for the financial support provided in the form of a senior research fellowship. Authors are thankful to DST-FIST for providing UV?Vis spectrophotometer, FTIR spectrometer.
Keywords: CaMoO4; Dy3+ ion; Energy transfer; Photoluminescence; Sm3+ ion